Vitamin E (α‐, β + γ‐ and δ‐tocopherol) levels in plant oils. (21st May 2020) - Aksoz, Elif; Korkut, Oguzhan; Aksit, Dilek; Gokbulut, Cengiz
Abstract: Vitamin E is the most potent lipid‐soluble antioxidant in human plasma. The richest sources of vitamin E are plant oils. This study aims to determine the concentrations of alpha, beta + gamma and delta‐tocopherols (α‐T, β + γ‐T and δ‐T) in various plant or seed oils commonly used in food, pharmaceutics or cosmetics. Forty‐one different plant or seed oil samples were purchased and kept at +4°C in the dark until the chromatographic analysis. Analyses were performed using high‐performance liquid chromatography (HPLC) following the dilution of the oil samples with 2‐propanol in a 1:3 ratio, without further processing. Total tocopherol levels in the oils analysed ranged from 11 to 3468 mg/kg. When the highest total tocopherol levels were taken into consideration, the first five plant oils were pomegranate seeds, wheat germ, fig seed, hippophae rhamnoides and corn oils. Moreover, the wheat germ, fig seed, safflower, sunflower and hazelnut oils had highest α‐tocopherol concentration in the oils analysed. These plant or seed oils have a high potential for using in the food, pharmaceutical and cosmetic industries due to their high tocopherol contents. Abstract : Alpha, beta + gamma and delta‐tocopherol concentrations in forty‐one different plant or seed oils were investigated. Highest total tocopherol levels were detected in pomegranate seed, wheat germ, fig seed, hippophae rhamnoides, and corn oils. Moreover, the wheat germ, fig seed, safflower, sunflower, and hazelnut oils have highest α‐tocopherol concentration in the oils analysed.